2019
DOI: 10.1098/rspb.2018.1281
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal symbiont populations in hydrothermal vent tubeworms and the environment

Abstract: Horizontally transmitted symbioses usually house multiple and variable symbiont genotypes that are acquired from a much more diverse environmental pool via partner choice mechanisms. However, in the deep-sea hydrothermal vent tubeworm Riftia pachyptila (Vestimentifera, Siboglinidae), it has been suggested that the Candidatus Endoriftia persephone symbiont is monoclonal. Here, we show with high-coverage metagenomics that adult R. pachyptila … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 48 publications
3
48
0
Order By: Relevance
“…Besides their putative function in effector protein export, symbiont membrane proteins may also lead to bacterial strain adaptation. The Riftia symbiont population is polyclonal, i.e., although there is only one 16S rRNA phylotype, this phylotype consists of several distinct strains (20). T4P system-mediated exchange of genetic material between different symbiont strains would add to this diversity in the symbiosis and might additionally enable exchange of symbiosis-related genes within the free-living “ Ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides their putative function in effector protein export, symbiont membrane proteins may also lead to bacterial strain adaptation. The Riftia symbiont population is polyclonal, i.e., although there is only one 16S rRNA phylotype, this phylotype consists of several distinct strains (20). T4P system-mediated exchange of genetic material between different symbiont strains would add to this diversity in the symbiosis and might additionally enable exchange of symbiosis-related genes within the free-living “ Ca.…”
Section: Resultsmentioning
confidence: 99%
“…The uncultured gammaproteobacterial Riftia symbiont, a single 16S rRNA phylotype tentatively named “ Candidatus Endoriftia persephone” (1921), densely populates bacteriocytes in the host trophosome, a specialized organ that fills most of the worm’s body cavity (14). The bacteria oxidize inorganic reduced compounds, such as hydrogen sulfide, to generate energy for carbon fixation (13, 2226).…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial housekeeping genes (atpA, recA, and gyrB) were selected (Polzin et al, 2019) for PCR amplifications with a set of custom primers ( Supplementary Table S2). DNA extracted from the guts was used as template.…”
Section: Multilocus Gene Sequencingmentioning
confidence: 99%
“…Although the symbiont population consists of a single 16S rRNA phylotype (comprising one dominating and several minor genotypes; Polzin et al, 2019 ), it was previously shown to exhibit remarkable metabolic versatility and redundancy: As demonstrated by proteomic analyses, symbionts from the same host animal expressed enzymes of two CO 2 fixation pathways, the Calvin cycle and the reverse tricarboxylic acid (rTCA) cycle, as well as enzymes for both glycogen generation and glycogen degradation ( Markert et al, 2007 ; Markert et al, 2011 ; Gardebrecht et al, 2012 ; Hinzke et al, 2019 ). Moreover, proteins involved in utilization of hydrogen sulfide and thiosulfate as energy sources were expressed simultaneously by the same symbiont population; as were proteins for the use of nitrate and oxygen as electron acceptors ( Markert et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%